2012
DOI: 10.1074/jbc.m112.371765
|View full text |Cite
|
Sign up to set email alerts
|

Steric Hindrance Mutagenesis in the Conserved Extracellular Vestibule Impedes Allosteric Binding of Antidepressants to the Serotonin Transporter

Abstract: Background:The serotonin transporter contains an allosteric binding site with unknown location. Results: We use molecular modeling, mutagenesis, and zinc site engineering to locate and inhibit the allosteric binding site. Conclusion: Data are consistent with the allosteric binding site being located in the extracellular vestibule. Significance: This opens the search for a new generation of antidepressant drugs directed toward the proposed allosteric binding site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
165
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(176 citation statements)
references
References 53 publications
11
165
0
Order By: Relevance
“…Overlap of high affinity inhibitor binding with the S1 site is supported by biochemical studies (38,44,47,55) and by recent structures of Drosophila (d) DAT and a LeuT/SERT hybrid co-crystallized with antidepressants (40,56). However, some DA transport inhibitors lack the charged nitrogen necessary to form the salt bridge with Asp-79 (57)(58)(59), suggesting that inhibitor binding can occur without this interaction and thus may not be limited to the S1 pocket (60). This possibility is supported by crystal structures of LeuT complexed at relatively low affinity with several selective serotonin uptake inhibitors (SSRIs) and tricyclic antidepressants (TCAs) in regions that overlap with S2 (16 -18, 56).…”
mentioning
confidence: 58%
“…Overlap of high affinity inhibitor binding with the S1 site is supported by biochemical studies (38,44,47,55) and by recent structures of Drosophila (d) DAT and a LeuT/SERT hybrid co-crystallized with antidepressants (40,56). However, some DA transport inhibitors lack the charged nitrogen necessary to form the salt bridge with Asp-79 (57)(58)(59), suggesting that inhibitor binding can occur without this interaction and thus may not be limited to the S1 pocket (60). This possibility is supported by crystal structures of LeuT complexed at relatively low affinity with several selective serotonin uptake inhibitors (SSRIs) and tricyclic antidepressants (TCAs) in regions that overlap with S2 (16 -18, 56).…”
mentioning
confidence: 58%
“…Recently, this notion was further supported by structures of the dopamine transporter (DAT) from Drosophila melanogaster and a LeuT/SERT hybrid protein co-crystallized with antidepressants (26,27). The role of the S2 binding site in substrate translocation is still a matter of debate, but it has recently been suggested that this region harbors a low-affinity allosteric binding site for antidepressants in SERT (28).…”
mentioning
confidence: 73%
“…Monoamine transporters have twelve transmembrane helices (TM) with TMs 1-5 and TMs 6-10 forming an invertedtopological repeat within which is a central binding site for substrate and ions approximately halfway across the membrane [7][8][9] . An extracellular vestibule in the outward-facing conformation 7,9,10 forms a secondary, allosteric site which, when occupied by ligands, can result in modulation of transporter activity by altering the kinetics of ligand dissociation from the central site [11][12][13] . Addictive substances such as cocaine and amphetamine bind to monoamine transporters and can either inhibit NT transport or promote NT efflux, respectively 14,15 .…”
Section: Main Textmentioning
confidence: 99%
“…It is made available under a The copyright holder for this preprint (which was not . http://dx.doi.org/10.1101/204859 doi: bioRxiv preprint first posted online Oct. 17, 2017; page 3 of 15 in modulation of transporter activity by altering the kinetics of ligand dissociation from the central site [11][12][13] . Addictive substances such as cocaine and amphetamine bind to monoamine transporters and can either inhibit NT transport or promote NT efflux, respectively 14,15 .…”
Section: Main Textmentioning
confidence: 99%